2005
DOI: 10.1007/s10562-004-0775-3
|View full text |Cite
|
Sign up to set email alerts
|

The activity and selectivity of oxygen atoms adsorbed on a Ag/?-Al2O3 catalyst in ethene epoxidation

Abstract: The bonding of the oxygen species held on a Ag/a-Al 2 O 3 catalyst has been studied by temperature programmed desorption and their reactivity in ethene epoxidation by temperature programmed reduction using ethene as the reductant. The Ag/a-Al 2 O 3 catalyst was produced by the thermal decomposition of a Ag oxalate/a-Al 2 O 3 precursor. Oxygen desorbs from this Ag/a-Al 2 O 3 catalyst in two states, one (peak maximum temperature 520 K) having a desorption activation energy of 140 kJ mol À1 -oxygen desorbing from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…The measured desorption temperatures of m/z = 44 amu are in line with those seen during similar TPR experiments on high surface area catalysts [23]. However, unlike results on high surface area catalysts we saw no m/z = 29 amu that would indicate partial oxidation products, in support of our theoretical simulations.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The measured desorption temperatures of m/z = 44 amu are in line with those seen during similar TPR experiments on high surface area catalysts [23]. However, unlike results on high surface area catalysts we saw no m/z = 29 amu that would indicate partial oxidation products, in support of our theoretical simulations.…”
supporting
confidence: 89%
“…Though the finding that the oxygen-induced p(2x1) reconstruction on silver strongly favors AcH production through an OMC mechanism, and ultimately combustion, is interesting, the analysis of temperature programed desorption (TPD) data suggests much of the oxygen on high surface area catalysts is adsorbed on close-packed faces [23]. And while the oxygen-induced reconstructions on the Ag(110) surface appear oxidic due to their linear Ag-O-Ag bonding motif, the oxygen-induced reconstructions on the Ag(111) surface are unlike any known bulk phases [16][17][18][19].…”
Section: Ethylene Oxidation On the P(4x4) Reconstruction Of Ag(111)mentioning
confidence: 99%
“…Thus, the average particle size of 0.12 lm determined by O 2 chemisorption at 170°C for the unpromoted Ag catalyst was assumed to be representative for all catalysts evaluated in this investigation. We conclude that because no apparent morphological changes in the Ag particles caused by addition of promoters were observed, the mechanism for higher EO selectivity must occur either through a site-blocking process, as stated by Waugh et al [6,[22][23][24], or through an electronic interaction, as proposed by Monnier and others [12,[25][26][27][28][29][30][31]33]. However, the results in Table 3 show that when 350 ppm of Cs is added to the AgARe catalyst, the required shell temperature to achieve 2.0 mol% EO drops from 262°C to 218°C, while the selectivity to EO increases from 49.85% to 82.35%.…”
Section: Discussionsupporting
confidence: 57%
“…A chlorine-containing moderator such as ethyl chloride (CH 3 CH 2 Cl) is also continuously fed to the reactor at ppm levels because it similarly increases the selectivity to EO. The use of Cs as a promoter has been discussed at length, but its specific role in the selective oxidation of ethylene is still the subject of considerable debate [22][23][24][25][26][27][28][29][30][31]. For example, Waugh and coworkers [6,[22][23][24] recently argued that the role of Cs is mainly geometric in nature and claimed that Cs is preferentially bound to Ag on unselective, stepped silver sites.…”
Section: Introductionmentioning
confidence: 99%
“…If the modified silver catalyst could produce the mild electrophilic oxygen species to attack the C=C bond of the alkenes, the catalyst would be highly effective for the epoxidation of propylene. By the kinetics studies of adsorption and desorption of O 2 over the modified Ag/aAl 2 O 3 catalyst, Atkins et al [10,11] found that Cl or Cs could weaken the strength of Ag-O bond and block the adsorption of oxygen onto the stepped Ag surface, resulting in the increase of the selectivity to ethylene oxide from 75% to 85%. Some patents claimed that the conversion of propylene of 1.5-12.6% and the selectivity to PO of 32-60% were achieved over the K, W, Re and Cl modified Ag/CaCO 3 , CaF 2 , CaHPO 4 , CaMoO 4 and BaTiO 3 catalysts [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%